1977
DOI: 10.1161/01.res.41.5.616
|View full text |Cite
|
Sign up to set email alerts
|

Large scale purification of hog renin. Physicochemical characterization.

Abstract: Renin was purified from 47 kg of hog kidney to produce enough enzyme for enzymatic and physicochemical characterization. The procedure included extraction at pH 3.5 in the presence of protease inhibitors, two ammonium sulfate precipitations, ion exchange chromatography on Sepharose-hexamethylenediamino-pepstatin gel, gel filtration, and isoelectric focusing. Renin, 2.3 mg, with a specific activity of 1,100 GU/mg of protein was obtained with about 70,000-fold purification and 16% overall recovery. The purity cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…Although the apparent molecular weight of renin by gel filtration or sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) has been reported to be in the 38 to 42 kDa range, [35][36][37] it has also been reported that renin in kidney tissue has variable degrees of glycosylation, which may account for the reported variations in molecular weight. 36,37 Inagami et al identified in rat and hog kidneys a renin form responsible for all renin activity with a molecular weight between 55 to 60 kDa when they avoided the acidification step during the purification procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the apparent molecular weight of renin by gel filtration or sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) has been reported to be in the 38 to 42 kDa range, [35][36][37] it has also been reported that renin in kidney tissue has variable degrees of glycosylation, which may account for the reported variations in molecular weight. 36,37 Inagami et al identified in rat and hog kidneys a renin form responsible for all renin activity with a molecular weight between 55 to 60 kDa when they avoided the acidification step during the purification procedure.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Inagami et al identified in rat and hog kidneys a renin form responsible for all renin activity with a molecular weight between 55 to 60 kDa when they avoided the acidification step during the purification procedure. 38,39 These investigators reasoned that the native form of renin in the kidney was a 60 kDa molecule, which was converted during extraction to 40 kDa renin by a sulfhydryl-dependent protease.…”
Section: Discussionmentioning
confidence: 99%
“…Because the complex of renin and the binding protein easily dissociates into their components at pH. 3.0 or pH 10. 5.…”
Section: Discussionmentioning
confidence: 99%
“…Standard curves were obtained with pure human renin (1 to 100 ng). In the same assay were run purified human renal inactive renin (I to 100 ng; see above, renin source V); pure mouse submaxillary gland renin (24) (10-10,000 ng); pure hog renin (25) (10- Enzymatic assay. In this assay we determined the ability of 4(1 and 4BI I monoclonal antibodies to inhibit the enzymatic activity of renin in various species.…”
Section: Inactive Renal Renin Inactive Renin Was Extracted Frommentioning
confidence: 99%